Global regulation of a sigma 54-dependent flagellar gene family in Caulobacter crescentus by the transcriptional activator FlbD. - Wu, J (1995)
Biosynthesis of the Caulobacter crescentus polar flagellum requires the expression of a large number of flagellar (fla) genes that are organized in a regulatory hierarchy of four classes (I to IV). The timing of fla gene expression in the cell cycle is determined by specialized forms of RNA polymerase and the appearance and/or activation of regulatory proteins. Here we report an investigation of the role of the C. crescentus transcriptional regulatory protein FlbD in the activation of sigma 54-dependent class III and class IV fla genes of the hierarchy by reconstituting transcription from these promoters in vitro. Our results demonstrate that transcription from promoters of the class III genes flbG, flgF, and flgI and the class IV gene fliK by Escherichia coli E sigma 54 is activated by FlbD or the mutant protein FlbDS140F (where S140F denotes an S-to-F mutation at position 140), which we show here has a higher potential for transcriptional activation. In vitro studies of the flbG promoter have shown previously that transcriptional activation by the FlbD protein requires ftr (ftr for flagellar transcription regulation) sequence elements. We have now identified multiple ftr sequences that are conserved in both sequence and spatial architecture in all known class III and class IV promoters. These newly identified ftr elements are positioned ca. 100 bp from the transcription start sites of each sigma 54-dependent fla gene promoter, and our studies indicate that they play an important role in controlling the levels of transcription from different class III and class IV promoters. We have also used mutational analysis to show that the ftr sequences are required for full activation by the FlbD protein both in vitro and in vivo. Thus, our results suggest that FlbD, which is encoded by the class II flbD gene, is a global regulator that activates the cell cycle-regulated transcription from all identified sigma 54-dependent promoters in the C. crescentus fla gene hierarchy.